Lateral Cephalometric Norms for Libyans - Ferial. A. Msallam; Bassma. M. Gandila; -Prof. Dr. Abudrrzag M. Zendah (Aljameai, 1970)
Abstract:Objective: To establish lateral cephalometric norms for young Libyans and to compare these with the published norms of other populations.Materials and Methods: Cross sectional study of a sample selected on the basis of a balanced face and Class I occlusion. Lateral cephalograms were taken of 136 young Libyan nationals by birth having white complexion. Study comprised 70 females and 66 males aged 10 to 18 years with a mean age of 14 years attending the Central Dental Clinic, Tripoli, Libya. The sample was selected based on satisfying certain criteria - i) Class I molar relation, ii) Average over jet / over bite, iii) Acceptable profile and iv) No previous history of orthodontic treatment. Twenty-two cephalometric landmarks were identified and traced in a standard manner.Results: Twenty-one variables representing linear and angular measurements were evaluated and subjected to statistical analysis which established the cephalometric norms for Libyans.Conclusion: The study revealed that Libyans have distinctly different cephalometric measurements compared to other populations including the Arabs. The Libyans have a flatter facial profile, prominent lips and a tendency for skeletal Class 2. The other significant findings in the Libyan population were noted to be an increased anterior facial height together with a marked dento- alveolar protrusion. Gender and age differences were limited and noted only in the linear variables.Key Words: - Cephalometric norms; Lateral cephalograms; Libyan facial features.المستخلص:الهدف: وضع معايير الأنسجة الصلبة الرأسية الجانبية للشباب الليبي ومقارنتها مع المعايير المنشورة لشعوب أخرى.المواد والطرق: دراسة مقطعية لعينة مختارة على أساس الوجه المتوازن والإطباق من الدرجة الأولى. تم أخذ صور رأسية جانبية لـ 136 شابًا ليبيًا بالولادة ذوي بشرة بيضاء. شملت الدراسة 70 أنثى و66 ذكراً تتراوح أعمارهم بين 10 سنوات إلى 18 سنة بمتوسط ​​عمر 14 سنة يراجعون العيادة المركزية لطب الأسنان طرابلس_ ليبيا. تم اختيار العينة بناءً على استيفاء معايير معينة : 1- العلاقة المولية من الدرجة الأولى. 2- متوسط ​​النفث / العضة. 3- المظهر المقبول. 4- لا يوجد تاريخ سابق لعلاج تقويم الأسنان.تم تحديد وتتبع اثنين وعشرين من المعالم الرأسية بطريقة قياسية.النتائج: تم تقييم واحد وعشرون متغيرا تمثل القياسات الخطية والزاوية وإخضاعها للتحليل الإحصائي الذي وضع معايير قياس الرأس لليبيين.الاستنتاج: كشفت الدراسة أن الليبيين لديهم معايير قياس رأسية مختلفة بشكل واضح مقارنة بالسكان الآخرين بما في ذلك العرب. "الليبيون لديهم مظهر وجه مسطح، وشفاه بارزة وميل للفئة الهيكلية 2. ولوحظ أن النتائج الهامة الأخرى في السكان الليبيين هي زيادة ارتفاع الوجه الأمامي مع نتوء سني سنخي ملحوظ. وكانت الفروق بين الجنسين والعمر محدودة ويلاحظ فقط في المتغيرات الخطية.